Sodelovanje med medicinskimi sestrami in zdravniki: - Strauss, Maja (Obzornik zdravstvene nege, 2018)
Introduction: Good cooperation between doctors and nurses enables a higher quality of patient treatment. The purpose of the study was to determine how students of medicine and students of nursing evaluate the relationships between nurses and doctors.Methods: In a non-experimental quantitative study, a Jefferson scale was used to evaluate co-operation between doctors and nurses. 428 students were included in a convenience sample of whom 235 (54.9 %) were nursing students and 193 (45.1 %) were medical students. The data were analysed with bivariate statistics and the t-test.Results: The findings have shown statistically significant differences regarding the gender of the respondents and with some claims also with respect to the students' study programme. The female respondents in general agreed more with the claims than the male respondents. The biggest difference regarding gender was with respect to the claim that students of medicine and nursing students should participate in teamwork during their studies, so that they could understand their roles better (t = 2.59, p = 0.010). In general, the nursing students agreed with the claims more than the medical students. Comparing the two study programmes, the greatest difference was found with respect to the claim that "The nurse should be seen as a doctor's co-worker and colleague, and not as a doctor's assistant" (t = 15.24, p < 0.001).Discussion and conclusion: The findings have shown statistically significant differences in the evaluation of the relationship between nurses and doctors according to gender and study programme. The differences in the views of the students from the two faculties provide an opportunity for future curriculum design of these two study programmes.
Keywords: healthcare professionals; sodelovanje; students; študentje; teamwork; timsko delo; zdravstveni delavci